The Effect of Perineal Massage on Third Trimester Pregnant Women in Preventing Perineal Rupture - Mita Stianto; Siti Fatimah; Fatmawati Fatmawati (Jurnal Keperawatan Profesional, 2026)
Perineal rupture is a common complication of vaginal delivery and can cause pain, bleeding, and impaired reproductive function that impacts the mother's quality of life after delivery. One non-pharmacological prevention effort that can be done is perineal massage in the third trimester of pregnancy to increase the elasticity of the perineal tissue. This study aims to determine the effect of perineal massage on the incidence of perineal rupture in pregnant women in the third trimester. Methods: The study used a quasi-experimental design with a pretest–posttest control group design model. The sample consisted of 30 pregnant women in the third trimester who were divided into an intervention group and a control group, each with 15 respondents. Control of confounding variables was carried out through inclusion criteria and the provision of the same initial education. Data analysis used the Mann–Whitney test. The results showed a p value = 0.021 (p <0.05), so Ho was rejected and H1 was accepted, so there was a significant effect of perineal massage on the incidence of perineal rupture in pregnant women in the third trimester.  The conclusion is that perineal massage is effective in reducing the incidence of perineal rupture, so it is recommended as part of education classes for pregnant women with the assistance of health workers